Two extraordinary troglobitic species of Allokoenenia (Eukoeneniidae: Palpigradi) from Brazil: first records of this initially monotypic genus more than a century after its description - Souza, Maysa Fernanda Villela Rezende; Ferreira, Rodrigo Lopes (European Journal of Taxonomy, 2022)
The diversity of Palpigradi is not evenly distributed among its different branches. The widespread genus Eukoenenia includes 80% of the species, while the other genera are poorly known. Allokoenenia certainly is the most understudied genus because it is represented only by the African species Allokoenenia afra Silvestri, 1913. Its description is short and does not include many features depicted in modern taxonomy of Palpigradi. In this paper, we describe two troglobitic species of Allokoenenia, report the occurrence of a third species represented by an immature specimen from Brazilian caves, and provide brief notes on the morphology of A. afra. Allokoenenia canhembora sp. nov., A. stygia sp. nov., and Allokoenenia sp. differ from A. afra by several morphological features, including more elongated appendages and a greater number of blades on lateral organs. Thus, they are considered troglomorphic. These new species are vulnerable to extinction because they are endemic to a single or few caves directly impacted by mining activities and groundwater exploitation. This study represents the first step for the conservation of these species and their habitats, since Brazilian caves with rare troglobites cannot be irreversibly impacted. Also, it brings important contributions on the distribution and morphology of this enigmatic genus.